Repeated measurements of depression and outcomes in patients receiving hemodialysis† - Zhang Lu; Zhang Su-Mei; Shi Sheng-Yan; Quan Hai-Ying; Yang Xiu (Sciendo, 2022)
Objective: Depression appears to be common among the patients with end-stage renal disease (ESRD). Therefore, how to comprehensively analyze the changes in depression and its impact on patient outcomes is an important research direction. The objectives of this study were to assess changes in depression and whether depression can be used to predict outcomes in patients receiving hemodialysis.